(3GdJfGgi hGdJMOjOs - (3GdMSjf Hf GdbGSe Hf Ydj GdYjGfj, GdegOj dOjf Gddg,J (B404 (3g` s
(3ChdgG (B:s
(3jHJOF HeSGFd ef GdeMGd ai Mb Gddg hGdQO Ydi GdeTHgI s
(3BNQgG (B:s
(3HBNQg PcQ ef JLH WGYJg ef GdPQjI GdeHGQcI s
(3hajg cJGH GdJhcd hcJGH GdWHGFYs
(3hcJGH ThGgO GdUfY hGdCOdIs
(3h cJGH GdQO Ydi GdedMOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B252s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B122 s
Keywords: (3GdJhMjO hGdedd hGdfMds